Моделювання роботи залізобетонних балок із композитною попередньо напруженою арматурою - Мацьопа, І. Р.; Мурин, А. Я.; Matsopa, I.; Muryn, A. (Видавництво Львівської політехніки, 2018)
У залізобетонних конструкціях за значного впливу агресивного середовища застосування попередньо напруженої арматури є достатньо проблемним питанням. На даний час є багато рекомендацій щодо зменшення впливу агресивного середовища на корозійні процеси в арматурі, збільшення надійності конструкцій та терміну їх придатності до нормальної експлуатації. Одним із варіантів вирішення проблеми є застосування в ролі арматури неметалевих елементів (як внутрішньої стержневої арматури, так і у вигляді наклеюваної зовнішньої). Для покращення фізико-механічних характеристик конструкції рекомендується застосування попереднього напруження, при цьому актуальними є питання розрахунку і оптимального проектування будівельних конструкцій з неметалевою арматурою (FRP). В Україні одним з лідерів моделювання є програмний комплекс “Лира” – сучасний інструмент для чисельного дослідження міцності і стійкості конструкцій.

Traditional building materials are regularly improved, finding new operational characteristics and complementing the quality of technical parameters. For a long time and now as reinforcement of reinforced concrete elements is steel. Corrosion of steel and conductiveness, prompted researchers to improve the quality of reinforcement, as a result of which non-metallic composite reinforcement was created. Composite materials are a group of reinforcing bars that differ in the type of feedstock, consisting of two or more components. The first element is fibers from various types of raw materials, the second is a thermosetting or thermoplastic polymer (resin). After the binder is cured, strong rods are obtained. There are five types of composite non-metallic reinforcement: fiberglass, basalt plastic, carbon fiber, hybrid, glass reinforced polyethylene terephthalate. Non-metallic element as replacements for internal rod, and gluing to the surface of reinforced concrete structures of composite tapes or fabrics. To improve the physical and mechanical characteristics of the structure, recommended applied the previous tension, calculation and optimal design of building structures with non-metal reinforcement (FRP) are relevant. For modeling of building structures, software package in which the implemented finite element method are used, the most famous of them are Ansys, Femap, Nastran, Lira, Scad, the last two are Ukrainian developers. In Ukraine, one of the leaders is the software complex “Lira” – a modern tool for numerical investigation of strength and stability of structures. Accounting for the non-linear operation of the structure allows building adequate design schemes, identifying additional reserves of bearing capacity, reducing material consumption to ensure structural safety. When calculating structures, physical nonlinearity are distinguished, in the calculation of the nonlinear dependence between the components of generalized stresses and strains.
Modelling of reinforced concrete beams with pretensioned frp reinforcement
Keywords: залізобетонна балка; композитна арматура; попереднє напруження; програмний комплекс “Лира”; нелінійний розрахунок; reinforced concrete beam; composite reinforcement; previous tension; software complex “Lira”; non-linear calculation; 624.012.46